Cross-protective humoral immunity to coronaviruses from SARS coronavirus 2–naïve sera of children with Kawasaki disease. (February 2023) - Lin, Tzu-Yi; Lee, Yu-Lin; Wu, Kun-Lang; Yang, Ming-Chun; Huang, Chi-Nan; Fu, Chun-Min; Huang, Li-Ming; Chang, Luan-Yin; Lin, Ming-Tai; Liu, Hong-Hsing
Abstract: Objectives: SARS coronavirus 2 (SARS-CoV-2)–associated multi-system inflammatory syndrome in children indicates that viruses can trigger a Kawasaki disease (KD)-like hyperinflammation. A plausible hypothesis was that coronavirus-specific 'holes' in humoral immunity could cause both diseases. Methods: To determine whether SARS-CoV-2–naïve patients with KD have inferior humoral immunity for the novel coronavirus, sera of children with KD and control children from year 2015 to 2021 were subjected to ELISA, microwestern, and neutralization assays to evaluate the capabilities in recognizing the receptor-binding domain of SARS-CoV-2, spotting spike proteins of three respiratory syndromic coronaviruses, and blocking SARS-CoV-2 from binding to angiotensin-converting enzyme 2 receptors in vitro, respectively. Results: 29 patients with KD before 2019, 74 patients with KD in 2019 or 2020, 54 non-febrile controls, and 24 febrile controls were included in the study. SARS-CoV-2 was recognized on ELISA for both patients with KD in 2016 and those with KD in 2020. Microwestern demonstrated cross-reactive IgG in an all-or-none manner towards three spike proteins of syndromic coronaviruses regardless of sample year or KD status. The ratio between the sera that recognized all spike proteins and those that recognized none (51 vs. 47) was significantly higher from patients with KD than from non-febrile controls (17 vs. 32; p 0.047) but not from febrile controls (13 vs. 11; p 0.85). Most positive sera (12 of 17 controls, 5 of 8 patients with KD before 2019, and 28 of 33 patients with KD in 2019 or 2020) offered protection comparable to low-titre sera from the WHO reference panel. Discussion: Humoral immunity of SARS-CoV-2–naïve children with KD was not inferior to that of controls in offering cross-protection against the novel coronavirus.